Many peoples, many faiths: women and men in the world religions - Ellwood, Robert S. (Routledge, Taylor & Francis Group, 2023)
"Many Peoples, Many Faiths places the world's religions in historical context, illustrating the complex dynamic of each religion over time, while also presenting current beliefs, practices and group formations. This unique textbook includes engaging sections on women in religion, religion governance, and religion in America throughout. Thoroughly revised and updated for its eleventh edition, Many Peoples, Many Faiths covers the following topics: Understanding the World's Religious Heritage Indigenous Peoples and Religion The Spiritual Paths of India The Journey of Buddhism Religions of East Asia The Family of the Three Great Monotheistic Religions and Zoroastrianism The Unique Perspective of Judaism The Growth of Christianity Building the House of Islam New Religious Movements Religion and Violence, Non-Violence, and Peacemaking. This edition reflects new scholarship and general interest and, where appropriate, addresses rapidly developing and shifting areas, taking account of the dynamic, changing quality of religion. New and expanded material on indigenous peoples and religions, discussions of colonization, and the new chapter on religion and violence, non-violence, and peacemaking also distinguish this edition. Images, maps, and timelines add to the sense of the richness of the world religions. This is an ideal resource for anyone wanting an accessible and yet comprehensive introduction to the world religions"--